The Recommendation of Ethnic Diversity in Late Habsburgian State and some Parallels in the Cultural Conception of the EU after 2004 - Prosser-Schell, Michael (Ethnographica et Folkloristica Carpathica, 2023)
First of all, the article discusses that the ancient Habsburgian state (end of 19th – early 20th century), which had explicitly recommended and fostered ethnic diversity, gains a benevolent interpretation in some important academic presentations nowadays. This seems remarkable because the late Habsburgian monarchy after 1919 until ca. 2000 was examined as a failed state. The article analyses, based on the famous and popular-written applied geography „Die österreichisch-ungarische Monarchie in Wort und Bild“ (called „Kronprinzenwerk“, 1981–1902), how the recommendation of ethnic diversity was framed and expressed in that time. The article especially wants to show the arguments in which the strength of the pluriethnic and pluricultural Habsburgian empire generally had to be reasoned. Furthermore, the paper chooses 3 specific cases of an affirmative regional and ethnic description of the „Kronprinzenwerk“: Ruthens in Galicia, Serbs and Germans („svabians“) in Southern Hungary of that time. Nowadays, we see a strikingly similar argument in the European Union to recommend ethnic and cultural diversity to achieve a consolidated socio-economic grouping. An outstanding and prominent example is the speech of French President Emmanuel Macron in 2017 at Sorbonne University.